(untitled) (Journal of Geography and Environmental Management, 2022)
The changes of glaciers in the basins of the Aksu-Bien and Lepsy-Baskan rivers in the northern part of the Zhetysu Alatau were studied for the periods 1956-2001, 2001-2012 and 2012-16, based on the analysis of Landsat TM/ETM+ and OLI data. In 2001, 245 glaciers with a total area of 197.2 km2 were discovered, by 2016 they had decreased to 232 glaciers with a total area of 165.5 km2, which is 31.7 km2 less, that is, 1% per year for 15 years. The rate of glacier reduction was also analyzed based on their differences in size, height and aspect of slopes, as well as other topographic parameters in five basins (Bien, Aksu, Sarkan, Baskan, Leps), where the reduction of glaciers varied from 14.9% to 17.5%. Such a high rate of reduction is probably related to the general trend temperature increases due to the fact that small glaciers are located at a relatively low altitude of the outer ridges of the Zhetysu Alatau. However, according to the results of our research, as well as the works of other authors who have studied this territory, the rate of reduction of the area of glaciers in the northern part of the Zhetysu Alatau is lower compared to other territories. We came to the conclusion that the glaciated areas of the Aksu-Bien and Lepsy-Baskan river basins are located in the most favorable conditions for glaciation – which is confirmed by the larger average sizes of glaciers that are higher than in other basins – and as a result showed a lower rate of reduction than other glaciated areas of the Zhetysu Alatau from 1956 to 2016.